Genetic factors in premature ovarian failure - Zavala Coca, Carlos (2015)
Premature ovarian failure (POF) is defined as the loss of function of the ovaries before age 40, causing amenorrhea, high FSH levels and low estradiol levels. This review describes the genetic factors that predispose to POF, including anomalies in chromosome X and chromosome fragile X, defects in autosomal genes and in genes involved in the maturation of the ovarian follicle.